Randomized controlled trial comparing outcome of hybrid Ilizarov versus distal tibial metaphyseal locking plate (P) for treatment of distal tibial fractures in adults - Sharma, Jeevan Kumar; Chaudhary, Pashupati; Rijal, Raju; Pokharel, Bishnu (International Journal of Research in Orthopaedics, 2018)
Background: Distal tibia fractures include extra-articular fractures of the metaphysis and the more severe intra-articular tibial plafond or pilon fractures.Several treatment methods have been recommended for the treatment of these injuries, with a recent emphasis on minimally invasive techniques and Ilizarov technique also. Several studies regarding distal tibial fracture treatment are available. Few of them are only randomized controlled trial. So, we conducted this research comparing distal tibial plating (P) versus hybrid Ilizarov (HI) for treatment of distal tibial fractures. Methods: The randomized controlled trial was conducted in B.P. Koirala Institute of Health Sciences, a tertiary care hospital in Eastern Nepal, over a period of fifteen months from June 2015 to August 2016. Patient in group A underwent HI fixation, and group B underwent P. Results: Gender ratio for male: female was 2.63 in HI, 1.35 in P group. Mean age was 47.03±15.93 and 42.1±12.788 for HI and P respectively. Most fractures in both group belonged to AO A3 type. Most surgeries were done at interval of 1 day to 1 week. Mean hospital stay was 6.43±4.545 and 4.93±4.676 for HI and P respectively. Mean Lower extremity functional score (LEFS) was 66.55 in HI and 67.15 in P group. Mean Percentage of maximal function (LEFS/80 *100) was 83.56. Three cases among 40 cases in P had infection but no infection in HI group was seen at the end of 12th week follow up. Conclusions: Our study showed that there is no significant difference in terms of LEFS criteria, union, fracture alignment, ROM (knee, ankle), infection and other outcome measures between HI fixation and P in the treatment of distal tibia fracture in adults.